EFFECT OF CAPITAL, SOCIAL CAPITAL, WORK EXPERIENCE AND TECHNOLOGY ON PRODUCTIVITY OF ARABICA COFFEE FARMERS IN SIAKIN VILLAGE - Yuliarmi, Melinda, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
Productivity is a comparison output and input. Capital and technology that affect productivity, and its application can be seen in production techniques. Work experience and productivity have a positive relationship, because the higher experience can increase work productivity. The concept of social capital arises from the thought the community cannot work individually. This study to determine effect of capital, social capital, work experience and technology on the productivity of Arabica coffee farmers and to know the variables of social capital as a moderating variable of capital influence on productivity. This sampling uses propotional random sampling. The method is done by non-participant observation, structured interviews and in-depth interviews. Testing instruments with validity and reliability tests. The data analysis technique used is factor analysis and moderation regression analysis. Based on the results, it is known that capital, social capital and work experience have a significant positive effect on the productivity of Arabica coffee farmers in Siakin Village. But technology does not affect productivity because farmers use more labor in the production process. The variable social capital is significant and strengthens the influence of capital on the productivity of Arabica coffee farmers in Siakin Village.